Teacher Opinions on the Applicability of Process Based Writing Approach - Deniz, Hacer; Demir, Sezgin (My University, 2019)
Process based writing approach that aims to grade it in order to facilitate the writing process is an approach based on the structuring and digestion of knowledge on the mind. İt aims to teach students how to use and improve writing skills. The purpose of this research is determining the opinions of the Turkish teachers about the applicability of the process based writing approach. The research was carried out in phenomenological form from qualitative patterns and analyzed data by content analysis method. The study group was determined on the basis of volunteerism through the gradual sampling method consists of 14 Turkish teachers working in Elazığ province. Face-to-face interviews were conducted with the semi-structured interview form developed by the researchers and the findings were tabulated by determining frequency distributions. As a result of evaluating the opinions of the Turkish teachers, it was found that there are serious difficulties and deficiencies about the applicability of the process based writing approach. These difficulties stem from problems such as excessive time in practice, lack of information on the subject during the preparatory phase, and the inability to learn artificial language skills.
Keywords: Eğitim; Eğitim Araştırmaları